Effect of Silver Diamine Fluoride and Proanthocyanidin on Mechanical Properties of Caries-Affected Dentin - Firouzmandi, Maryam; Shafiei, Fereshteh; Jowkar, Zahra; Nazemi, Fereshteh (European Journal of Dentistry, 2019)
Objectives Inner carious dentin is specified with decreased minerals and collagen cross-links but without protein denaturation. Current minimally invasive dentistry concepts recommend removal of only the outer layer of carious dentin and biomodification of repairable inner carious dentin. The present study aims to investigate the possibility of functional repair of this layer using silver diamine fluoride (SDF) and grape seed extract (GSE).Materials and Methods Molar teeth with occlusal caries were used to prepare caries-affected dentin specimens for hardness and elastic modulus measurements. The specimens of each test were divided randomly into four equal groups. In the GSE group, the specimens were immersed in 6.5% GSE solution for 10 minutes. In the SDF group, the specimens underwent a topical application of a 30% SDF. In the GSE+SDF group, first the specimens were immersed in GSE and then exposed to SDF. In the SDF+GSE group, first SDF was applied and then the specimens were immersed in GSE. Microhardness measurements were taken at baseline and after treatment. A control group with distilled water treatment was also prepared for elastic modulus measurements.Statistical Analysis One-way analysis of variance and post-hoc tests were used for statistical analysis.Results There were significant differences in H1-H0 (final hardness—baseline hardness) among the groups. Baseline and final hardness of each group was also significantly different (SDF>SDF+GSE>GSE>GSE+SDF). Elastic modulus of SDF and SDF+GSE increased compared to the control group.Conclusions SDF and SDF+GSE treatment can be recommended to increase hardness and elastic modulus of caries-affected dentin.
Keywords: silver diamine fluoride; grape seed extract; Knoop hardness; modulus of elasticity; caries-affected dentin